2015
DOI: 10.17671/btd.55726
|View full text |Cite
|
Sign up to set email alerts
|

İstanbul Borsası’nda İşlem Gören Firmaların Finansal Performanslarının Kümeleme Analizi ile Değerlendirilmesi

Abstract: Özet-Firmalar içinde bulundukları sektörlere göre birtakım faaliyetler gerçekleştirmektedir. Bu faaliyetlerinin dökümü olan finansal tablolar ise firmalara geçmiş faaliyet dönemi hakkında fikir vermekte, sonraki dönemler için atacağı adımları ve alacağı tedbirleri şekillendirmektedir. Gelişen bilişim teknolojileri kullanıcılarına çok büyük veriler üzerinde son derece önemli analizler yapma imkânı tanımaktadır. Bu analizler sayesinde firmalar mevcut duruma dair görüntüler elde etmekte, geleceğe dair senaryolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Used Çetin and Irmak [20] the twostage clustering method to categorize bank customers according to demographic information such as education level, age, and occupation. Arı et al [21] used two-stage clustering analysis in their study to determine the perceptions of security and risk in electronic shopping by academics from 40 different universities. As a result of the cluster analysis, they concluded that the participants gathered in 4 different clusters according to their risk perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Used Çetin and Irmak [20] the twostage clustering method to categorize bank customers according to demographic information such as education level, age, and occupation. Arı et al [21] used two-stage clustering analysis in their study to determine the perceptions of security and risk in electronic shopping by academics from 40 different universities. As a result of the cluster analysis, they concluded that the participants gathered in 4 different clusters according to their risk perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akyuz et al (2012) used the alignment of clusters via financial ratios of manufacturing firms with their respective sectors. Ozkan and Boran (2014) examined clusters of firms in the manufacturing sector, while Ari et al (2016) and Gazel and Akel (2018) analyzed the financial performance and sector classification compatibility of firms listed on BIST (Borsa Istanbul).…”
Section: Introductionmentioning
confidence: 99%